Major Stress-Strain State of Double Support Multilayer Beams Under Concentrated Load. Part 2. Model Implementation and Calculation Results - Kovalchuk, S.B.; Goryk, O.V. (Проблеми машинобудування, 2019)
The purpose of this paper is to design an analytical model for bending double support multilayer beams under a concentrated load, with the model based on the previously obtained elasticity theory solution for a multi-layer cantilever. The second part of the article contains examples of the implementation of the model for bending double-support multi-layer beams under a concentrated load, with the model constructed in the first part of the article. Using this model, solutions to the problems of bending multi-layer beams with different types of fixation of their extreme cross-sections were obtained. Метою даної роботи є побудова аналітичної моделі вигину двохопорних багатошарових балок під дією зосередженого навантаження на основі отриманого раніше розв’язку теорії пружності для багатошарової консолі. У другій частині статті наведені приклади реалізації моделі згину двохопорних багатошарових балок під дією зосередженого навантаження, побудованої у першій частині статті. Із використанням моделі отримано розв'язки задач згину багатошарових балок з різними способами закріплення їх крайніх перерізів. Целью данной работы является построение аналитической модели изгиба двухопорных многослойных балок под действием сосредоточенной нагрузки на основе полученного ранее решения теории упругости для многослойной консоли. Во второй части статьи приведены примеры реализации модели изгиба двухопорных многослойных балок под действием сосредоточенной нагрузки, построенной в первой части статьи. С использованием модели получены решения задач изгиба многослойных балок с различными способами закрепления их крайних сечений.